If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X+3=-4X-42
We move all terms to the left:
X+3-(-4X-42)=0
We get rid of parentheses
X+4X+42+3=0
We add all the numbers together, and all the variables
5X+45=0
We move all terms containing X to the left, all other terms to the right
5X=-45
X=-45/5
X=-9
| 3.5/x=140 | | 5+3x-4x^2=4 | | 1x+10=40 | | 2r+3/2 =5 | | 2r+3 =5 | | 50+116+(x+26)+x=360 | | 6r−12/3 =6 | | 20-5x=7x | | 5(k−3)=20 | | 5(k−3)=20. | | 4k+7=2k+25. | | r+1/2 =4 | | (b−7)/3 =6 | | 3(b−7) =6 | | 7/5=d/ | | 34-w=274 | | 8=23-3x | | 8p^2-22p+5=0 | | 3(3)-14=x-8 | | 6(v+3)=62 | | y-5.5=4.4 | | w+2.13=7.29 | | 15+3x=48 | | w-5.7=7.1 | | 3c+12=6c+10.74 | | c+2/3=-21/2 | | -5t^2+20t=60 | | -49x^2+(5x-3)^2=0 | | -5t^2+20=60 | | 12=5/2w | | (5x-3)^2=49x^2 | | 6+2/3x=11-x |